Model of a Photovoltaic Module for the MatLab/Simulink SimPowerSystems Library - D. I. Zalizny (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The relevance of research is caused by the increase of the number of photovoltaic power plants in the Republic of Belarus and, accordingly, the need to solve problems of diagnostics of photovoltaic modules. A new Simulink model of a photovoltaic module focused on using the standard SimPowerSystems library of power supply system elements (a part of the MatLab/Simulink) is proposed. The model allows altering solar irradiation values for each solar cell of the module. The use of the model also makes it possible to obtain calculated values of voltages and currents at the photovoltic module output. In addition, the model provides the simulation of individual solar cells shading in the module. The developed Simulink model operates on the base of a well-known exponential dependence describing the volt-ampere characteristic of a photovoltaic module, and also takes into account the real circuit of the module with bypass diodes. The series resistance of the photovoltaic module is calculated by the subtraction between its experimental and theoretical volt-ampere characteristics for conditions that are close to normal. The Simulink model of the SF-P672300 module contains 72 nonlinear elements implemented on the basis of controlled current sources and connected in series. The model solved the problems of the algorithm stability for calculating algebraic cycles by introducing constraint the current and the voltage parameters. Experimental studies for the fully illuminated and partially shaded SF-P672300 module have demonstrated that the maximum relative error of the developed Simulink model does not exceed 15 %. Experimental and theoretical current-voltage characteristics of the SF-P672300 module under full illumination and partial shading are presented. The presented Simulink model may be used both at the design stage and at the operation stage of photovoltaic power plants in order to simulate and analyze the factors that affect the operation of them.